The significance of evaporation heat and mass transfer through a spray sheet with two-phase transitional momentum transport and vapour dispersion - Ahmed Abed Al-Kadhem Majhool; Ammar Muslim Hadi; Faris Alqurashi; Sara Falih Kareem; Noor M. Jasim; Mujtaba A. Flayyih (International Journal of Thermofluids)
Until now, there has been a lack of two-phase velocity and vapor investigations under the evaporation condition. Therefore, this work addresses this title in order to be additive to this subject. The spray droplets are modelled using the moments method, and the gas phase is modelled using the Eulerian approach. The spray drag, breakup, and evaporation sub-models are taken into account. Based on the RANS turbulence model for the carrier gas phase and a calibrated atomisation model for the dispersed droplets, turbulence closure is accomplished. The spray tip penetration is evaluated and compared with experimental data. The fuel vapour mass fraction is calculated by using a transport equation for the droplet-gas interaction. The distribution of the fuel vapour mass fraction is compared with the KIVA code. Fortunately, there are no experimental results for the spray or gas velocity to be compared with. All presented results are investigated by their variation with positions and time to give the total behaviour. The fuel vapour mass fraction distribution exhibits a bell-shaped behaviour. In close proximity to the injector, the evaporation rate is significantly higher. There was no significant increase in the evaporation rate of the pressure swirl nozzle as the distance from the injector increased. During the evaporation of spray droplets, higher fuel vapour concentrations are present at the core spray than at the peripheral edge. The droplet velocities in the outer edge’s axial and radial directions display a reduced magnitude. The droplet’s diameter is greater at the inner edge than at the outer edge. The comparisons showed that there was good agreement with both the experimental and numerical results.